1996
DOI: 10.1007/bf01372240
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurement of renal length in children: Does the position of the patient matter?

Abstract: Sonographic measurements of renal length made with the patient lying supine or in contralateral decubitus yield slightly higher values than those made with the patient prone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 15 publications
5
23
1
Order By: Relevance
“…The state of bladder filling should especially be noted on serial ultrasounds and compared to the previous study when worsening HN is detected (19). Similarly, comparisons of renal length or APD between serial studies should be consistent with the patient positioning, as the prone views CUAJ -CUA Guideline Capolicchio et al Guideline: Antenatally detected hydronephrosis can differ from the supine or decubitus views (20). Fasting for a RBUS is both unnecessary and unpleasant.…”
Section: Renal -Bladder Ultrasound (Rbus)mentioning
confidence: 99%
“…The state of bladder filling should especially be noted on serial ultrasounds and compared to the previous study when worsening HN is detected (19). Similarly, comparisons of renal length or APD between serial studies should be consistent with the patient positioning, as the prone views CUAJ -CUA Guideline Capolicchio et al Guideline: Antenatally detected hydronephrosis can differ from the supine or decubitus views (20). Fasting for a RBUS is both unnecessary and unpleasant.…”
Section: Renal -Bladder Ultrasound (Rbus)mentioning
confidence: 99%
“…Furthermore, several reports have shown that, depending on the patient position, the measured maximal longitudinal length varies. Carrico, De Sanctis and Nakamura showed that supine, coronal views yield longer renal measurements than prone, sagittal views [3,[6][7][8]. Carrico and De Sanctis did not propose an explanation for the reported position-related differences.…”
Section: Discussionmentioning
confidence: 88%
“…Schlesinger showed, however, that variations in renal length can be measured that are equal to the normal increase in renal length that occur in 1-2 years, suggesting that ultrasonography is limited for evaluating renal growth [5]. In addition, several studies have shown that the measured maximal longitudinal renal length varies with the used imaging plane as well as with the patient position [3,[6][7][8]. De Sanctis and Nakamura showed that coronal views in the contralateral oblique position and sagittal views in the supine position yield longer renal lengths than sagittal views in the prone position [3,7,8].…”
Section: Introductionmentioning
confidence: 97%
“…At our institution, kidneys were measured in supine position. Ultrasounds performed at outside institutions may have used a different technique; however, only three ultrasounds were performed at outside institutions, and any differences between prone and supine measurements are likely to be small (24). Additionally, RPA measurements were adjusted for the scale of the images.…”
Section: Discussionmentioning
confidence: 99%